"Effect of Cryotherapy on Physiologic Pigmentation of Oral Mucosa: A Preliminary Study " - A. Darbandi; N. Amel Shahbaz (Tehran University of Medical Sciences, 2004)
Statement of Problem: Physiologic pigmentation of oral mucosa is considered as a prevalent entity among black people and those having relatively dark skin. Gingival physiologic pigmentation may cause problems for some patients specially ladies as far as esthetics is concerned. To overcome the issue, the surgery might be suggested which can cause some problems due to its side effects. Cryotherapy which is recently suggested for removal of such pigmentations has more advantages like quickness, simplicity, lack of bleeding and scar compared to other methods. Purpose: In this research, the objective was to analyze the effects of cryotherapy on physiologic pigmentations of oral mucosa. Materials and Methods: In this study, ten patients who had oral mucousa physiologic pigmentation were selected and a questionnaire was filled out for every one of them. The location and extent of every lesion was determined and local anesthesia was obtained by supraperiostal infiltration. By applying nitrogen oxide (with the temperature of 89.5°C) and using a suitable probe of equal size of lesions, they were frozen for 20-30 seconds. Then patient were examined on the 2nd and 7th day, 2nd and 4th week post-operatively. Results: After four weeks all pigmented parts were cured and no recurrent lesion was observed in any of patients. Conclusion: Oral cavity is an ideal environment for cryotherapy and it can be used as an effective method for treating oral pigmentation and some other oral lesions.